Pelatihan Publikasi Jurnal Ilmiah Bagi Mahasiswa-Mahasiswi Peserta Penelitian Dan Pengabdian Kepada Masyarakat International Di Wini - Dominikus Yordan Taboy; Alfianus Juventus Bria; Rivaldi Bastiano Hani; Gedarius Ezra; Guerikus Irwandi Tahu; Antonio Quenser; Siprianus Soleman Senda; José Albertino dos Santos; Marciana Martins; Claudiana Goncalves de Fatima; Judith Luciana Belo; Alvaro Soares; Evi Cesar Magno (CV. Multi Kreasi Media, 2025)
Scientific Journal Publication Training is the first step for students to understand the importance of writing articles and publication in scientific journals. This training is an effective step and has a positive impact so that students can understand how to write good and correct articles and improve students' skills and knowledge in writing scientific articles. The target of this training is for students of the Faculty of Philosophy, Widya Mandira Catholic University Kupang and Instituto Superior De Filosofia e De Teologia Dili who are carrying out International Research and Community Service activities. The purpose of this training is to answer students' problems in writing scientific articles, namely the lack of understanding of writing good and correct scientific articles, so that with this training, students from both institutions can understand about writing scientific articles and AI as the output of PPKM activities published in the OJS and Sinta Journals. The training methods used are lecture/socialization methods, discussions and exercises, practice writing scientific articles while doing community service and submitting articles to scientific journals. The results of this training are that several groups of students have succeeded in publishing PPKM articles in Sinta accredited journals.